Professional experiences of spanish advanced practice nurses: qualitative research - Yolanda Cantón-Rodríguez; Olivia Ibáñez-Masero; E. Begoña García-Navarro; Ángela María Ortega-Galán; María Isabel Ventura-Miranda; María Dolores Ruiz-Fernández (BMC, 2024)
Abstract Background Advanced practice nursing has emerged as a result of the evolution of healthcare systems, the changing needs of the population and the academic development of nursing, as well as sociodemographic and epidemiological changes. The aim of this study is to describe the professional experiences of Spanish advanced practice nurses in specific positions within the healthcare system in order to better understand the development and characteristics of this specialised nursing role. Methods A descriptive qualitative study was conducted. Fourteen advanced practice nurses from healthcare centres participated. Semi-structured interviews were carried out. Braun and Clarke's method for reflexive thematic analysis was followed. The Atlas. Ti version 22 program was used for technological support. The COREQ checklist was used to optimise the reporting of this qualitative study. Results From the analysis of the data collected, three themes and six subthemes were extracted: 1) Advanced practice nursing on the rise: (a) The driving forces in the development of advanced practice nursing, (b) Barriers to the development of advanced practice nursing; 2) Advanced practice nurses as a response to the population's needs: (a) The development of a new professional nursing role, (b) The patient at the centre of care in advanced practice nursing; 3) Training as the foundation for advanced practice nursing: (a) Expert nurses in a specific context, (b) Differences in the level of training depending on the context. Conclusion Advanced practice nurses have faced countless barriers and difficulties that have impeded them from demonstrating their importance and effectiveness within the healthcare system. A stable regulatory framework for the functions of advanced practice nurses is required to promote care, training and research in the field of advanced practice nursing. Health institutions need to promote the role of advanced practice nurses, facilitate the employment of new professionals, and establish new areas of practice. Trial registration Not applicable.